Experience of Saudi Female Undergraduate Nursing Students in a Psychiatric Clinical Setting - Reboldera, Melanie; Donato, Maria Flordeliza; Baratas, Gremma; Mulit, Gemma (Celebes Nursing Journal, 2026)
Introduction: Psychiatric clinical exposure is often perceived as highly stressful for nursing students due to the complex psychosocial and behavioral needs of patients, as well as the stigma commonly associated with mental health care. These factors can heighten anxiety and hinder students’ learning and professional development. Objective: This study aimed to explore the experiences of Saudi female undergraduate nursing student in a psychiatric clinical setting. Methods: A descriptive qualitative design was employed. Using convenience sampling, nine Saudi nursing students who had completed their psychiatric clinical rotation and demonstrated adequate English comprehension participated in a focus group discussion conducted in May 2022 in the Eastern Province of Saudi Arabia. Data were analyzed using Braun and Clarke’s six-phase thematic analysis. Results: Four themes and eight subthemes emerged: Stigma in Psychiatric Settings, Barriers to Care, Adaptation in Psychiatric Settings, and Transformative Effects of Psychiatric Experience. Subthemes included Unconscientious Individuals, Fearful Environment, Disease Processes, Limited Psychiatric Competence and Exposure, Strategies, and Assistance. Conclusion: The findings highlight that psychiatric hospitals provide both challenging and transformative learning experiences for nursing students. To optimize educational outcomes, nursing administrators and educators should strengthen protocols and guidelines for psychiatric clinical placements and recognize the essential role of clinical instructors and staff nurses, whose guidance and support are critical to fostering students’ personal and professional growth.